Spanish validation of the Parental Psychological Control Scale and Parental Psychological Control-Disrespect Scale - Carmen Rodríguez-Menéndez (Acta Colombiana de Psicología, 2021)
The construct "parental psychological control" has been used to refer to those parental behaviors that interfere with the children's thoughts and feelings. Examples of this type of behaviors would be inducing guilt or shame as well as the withdrawal of affection. The objective of this study was to validate and adapt the Spanish version of the Psychological Control Scale-Youth Self-Report (PCS-YSR) and the Psychological Control-Disrespect Scale (PCDS) and to analyze if the parental psychological control is defined as one dimension or two dimensions through manipulative and disrespectful behaviors towards adolescents. Also, the unique contribution of parental psychological control in predicting adolescent's self-concept was examined. In two samples of undergraduate university students (the first, N = 367, mean age = 19.8, women=62.7%, men=37.3%, and the second, N= 312, mean age=19.7, women=73.9%, men=26.1%), exploratory and confirmatory factor analyses confirmed the hypothesized factor structure of the PCS-YSR and the PCDS, for both paternal and maternal ratings. Convergent validity was confirmed by consistent associations between both measures of parental psychological control and other measures of parental autonomy support and parental psychological control. The multi-group analysis confirmed that parental psychological control had a negative influence on self-concept. The results indicated that both scales are useful instruments for assessing parental psychological control.